ECOLINGUISTIC APPROACHES TO THE STUDY OF GERMAN-LANGUAGE MEDIA SPACE - PIANKOVSKA, Iryna (Linguistic and Conceptual Worldviews, 2022)
The article covers the concepts of media linguistics and media ecology as the leading areas of modern media studies, their terminology and issues. Different approaches to the definition of media ecology are given and its role and tasks in different spheres of life are indicated. The scientific achievements of some Ukrainian and German linguists and media experts in the field of studying the German media space are analyzed in order to find ways of positive influence of mass media on society, in particular the influence of media ecology on media competence, cultural and ethical norms, communication between all members of society. The importance of studying the strategies and tactics of the influence of the media on the consolidation and isolation processes in society is emphasized. In addition, the article provides a linguistic analysis of the coverage of one of the most pressing global problems of today - coronavirus vaccination - in the German media source "ZEIT ONLINE" in order to establish its impact on the life of German society. In particular, the most commonly used lexical items and phrases are identified, which reflect the main topics of this problem, namely: compulsory vaccination, attitude of citizens to vaccination, dismissal of unvaccinated citizens from work or even dismissal, vaccination of children, government measures to prevent coronavirus and more. It is established that the coverage of the problem of vaccination in the German media is a clear example of the isolating impact of the media on society, as this issue is debatable and causes a lot of controversy during the discussion. In conclusion, it is noted that the use of appropriate means, in particular linguistic, in the media can significantly affect social processes, both isolation and consolidation. Possession of strategies and tactics of influence is crucial for the formation of public opinion on the global problems of mankind and the direction of its life.
Keywords: media linguistics, media ecology, German media space, linguis¬tic analysis, isolating influence of mass media